Two new species of the marine flatworm Pericelis (Platyhelminthes: Polycladida) from southwestern Japan with an amendment of the generic diagnosis based on phylogenetic inference. Issue 9 (26th November 2021) - Tsuyuki, Aoi; Oya, Yuki; Kajihara, Hiroshi
ABSTRACT: We describe two new polyclad species, Pericelis lactea sp. nov. and P. maculosa sp. nov., from Japan. Pericelis lactea sp. nov. is characterized by (i) a translucent white body, (ii) the male and female gonopores opening separately and (iii) a conical penis papilla. Pericelis maculosa sp. nov. is distinguished from its other congeners by (i) a translucent white body with white to light blue dots all over the dorsal surface and brown speckles around the pharyngeal area, (ii) the male and female gonopores opening separately and (iii) a long, cylindrical penis papilla. We also infer the phylogeny of 10 species of Diposthidae using a concatenated dataset comprising partial 18S and 28S rDNA sequences from the two new and eight other known species. Our results showed Marcusia alba Cuadrado, Rodríguez, Moro, Grande and Noreña, 2021 was nested within a clade comprising the seven Pericelis species included in the analysis. These findings support the prior synonymization of Marcusia with Pericelis based on the morphology, hence we transferred M. alba to Pericelis . We modified the diagnosis of Pericelis to accommodate such species as P. alba comb. nov. and P. lactea sp. nov., in which marginal eyespots are distributed only anteriorly. http://zoobank.org/urn:lsid:zoobank.org:pub:14906638-970B-4C67-81EE-E6111F98F77F